Poverty-Related Quality of Life among Community Dwellers in Barangay Poro, City of San Fernando La Union, Philippines: A Self- Reported Study - Tanko Titus AUTA; Paolo C. Colet (Humanistic Network for Science and Technology (HNST), 2018)
Poverty and inequality remains a significant problem in spite of the economy’s swift stride of growth over the past two years in Philippines. This study aimed to assess the poverty-related quality of life among community dwellers in Barangay Poro, City of San Fernando La Union, Philippines. A cross-sectional study using the poverty-related quality of life questionnaire was administered to 99 respondents. Overall, the global index score for the poverty-related quality of life among the respondents was 57.09±9.71. Aged 41-50 years had a significantly poorer relationship with family compared with those who were 31- 40 years old (p